Pulsed magnetic system of the relativistic electron beam accelerator «Temp-B» - Batrakov, A.B.; Glushko, Е.G.; Zinchenko, A.A.; Lonin, Yu.F.; Ponomarev, A.G.; Fedotov, S.I. (Вопросы атомной науки и техники, 2013)
The paper presents the magnet system for electron beam focusing and transport developed, manufactured and applied in this work including: an inductive sensor for magnetic field strength measurement, having characteristics similar to those of the Hall sensor, with which a map of the magnetic field in the accelerator diode has been obtained; a synchronizer designed to control the accelerator magnetic field triggering in the wide time interval; a stand for Rogovski loop calibration, used for noncontact measurement of the current in magnetic field solenoid coils.